If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + (2x + -10) = 0 Reorder the terms: 3x + (-10 + 2x) = 0 Remove parenthesis around (-10 + 2x) 3x + -10 + 2x = 0 Reorder the terms: -10 + 3x + 2x = 0 Combine like terms: 3x + 2x = 5x -10 + 5x = 0 Solving -10 + 5x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 5x = 0 + 10 Combine like terms: -10 + 10 = 0 0 + 5x = 0 + 10 5x = 0 + 10 Combine like terms: 0 + 10 = 10 5x = 10 Divide each side by '5'. x = 2 Simplifying x = 2
| 12x-92=-2+118 | | 20x-30y=50 | | -58+9x=3x+20 | | 4x^2-9y^2+18y-45=0 | | 2x-75=-12x+107 | | 0=-2*sin(2x) | | 19/2-[9/2{5/2-9/2-4}] | | (x+0.05)y=1.05y*x | | -41-x=19-5 | | X-7=x+19 | | 3w+3x=99 | | 3k^2-12k+12=75 | | -20+4x=43+x | | 2w+1x=49 | | 3k(k+1)=0 | | 9x-2=6x+13 | | 2x^2-5x-3=-3 | | 2x-5y+5xy=14 | | 2xy-5y+5xy=14 | | 36x-54+49=0 | | 2x^4/6x^2 | | y=32x+2 | | y=22x+1 | | 22=ax+1 | | 16-3x=36-8x | | 2x+7=19-2x | | 5ab+3ba= | | x/=6 | | so/ve | | y=x^3+9x-1 | | 3x+11=-17-4x | | 28p=70 |